Influence of clove oil and eugenol on muscle contraction of silkworm (Bombyx mori) - Kantaporn Kheawfu (2018)
Clove oil is used in fish anesthesia and expected to have a mechanism via glutamic receptor. The present study explores the activities of clove oil and its major compound, eugenol, in comparison with L-glutamic acid on glutamic receptor of silkworm muscle and fish anesthesia. It was found that clove oil and eugenol had similar effects to L-glutamic acid on inhibition of silkworm muscle contraction after treated with D-glutamic acid and kainic acid. Anesthetic activity of the test samples was investigated in goldfish. The results demonstrated that L-glutamic acid at 20 and 40 mM could induce the fish to stage 3 of anesthesia that the fish exhibited total loss of equilibrium and muscle tone, whereas clove oil and eugenol at 60 ppm could induce the fish to stage 4 of anesthesia that the reflex activity of the fish was lost. These results suggest that clove oil and eugenol have similar functional activities and mechanism to L-glutamic acid on muscle contraction and fish anesthesia.